A combination of ceftaroline and daptomycin has synergistic and bactericidal activity in vitro against daptomycin nonsusceptible methicillin-resistant Staphylococcus aureus (MRSA). Issue 5 (4th May 2017) - Shafiq, Iffat; Bulman, Zackery P.; Spitznogle, Sarah L.; Osorio, Justin E.; Reilly, Irene S.; Lesse, Alan J.; Parameswaran, Ganapathi I.; Mergenhagen, Kari A.; Tsuji, Brian T.
Abstract: There is an urgent need to optimize therapeutic options in patients with methicillin-resistant Staphylococcus aureus (MRSA) bacteremia who have failed conventional therapy. Two clinical isolates were obtained from a 68-year-old male with persistent MRSA bacteremia before and after the development of daptomycin nonsusceptibility. The pharmacodynamic activity of monotherapies and combinations of ceftaroline, daptomycin, cefoxitin, nafcillin and vancomycin were evaluated in time-kill experiments versus 10 8 CFU/mL of the pre- and post-daptomycin nonsusceptible MRSA isolates. Cefoxitin, nafcillin and vancomycin alone or in combination with ceftaroline failed to generate prolonged bactericidal activity against the post-daptomycin nonsusceptible isolate whereas a ceftaroline–daptomycin combination resulted in 6, 24 and 48 h log10 (CFU/mL) reductions of 3.90, 4.40 and 6.32. Population analysis profiles revealed a daptomycin heteroresistant subpopulation of the pre-daptomycin nonsusceptible MRSA isolate that expanded by >10, 000× on daptomycin agar containing 2–16 mg/L in the post-daptomycin nonsusceptible isolate. Daptomycin and ceftaroline combinations may be promising against persistent MRSA bacteremia.